Beyond Borders and Genders: Unveiling Cultural Influences on Badminton Motivation Among Older Adult Players in Taiwan and the United States - Wei-Chieh Liao; Yun-Di; David Cabello-Manrique; Chia-Min Wang; Li-An Liao (MDPI AG, 2024)
This study explores and compares the motivations behind badminton participation among older adult players from Taiwan and the United States (U.S.), with a specific focus on cultural and gender differences. A total of 139 participants aged 60 and above took part in the study, with 55 from the United States (24 females, 31 males) and 84 from Taiwan (39 females, 45 males). Utilizing the Exercise Motivations Inventory-2 (EMI-2), this research examines differences in motivations across cultural and gender lines, identifying key factors such as health-related motivations, personal achievement, social interactions, and competition. The results reveal that Taiwanese players are more motivated by health benefits and stress reduction, while U.S. players emphasize personal achievement and recognition. Additionally, gender-specific motivations emerged, with female players from both countries placing greater importance on social interactions compared to their male counterparts. These findings underscore the need for culturally and gender-sensitive approaches to promote sports participation among older adults in diverse settings.